Hepatic functional pathophysiology and morphological damage following severe burns: a systematic review and meta-analysis - Tapking, Christian; Kilian, Katja; Hundeshagen, Gabriel; Haug, Valentin; Teufel, Andreas; Houschyar, Khosrow Siamak; Kneser, Ulrich; Hirche, Christoph (Journal of burn care & research, 2022)
Severe burns are devastating injuries affecting multiple organ systems. Little is known about the influence on the hepatic system and its physiology. This systematic review aimed to assess the current state of research on morphologic liver damage following severe burns. A search was conducted in PubMed, Web of Science, and Cochrane databases using PRISMA guidelines. Outcomes included serum levels of transaminases, fatty infiltration, and necrosis. Weighted individual study estimates were used to calculate pooled transaminase levels and necrosis/fatty infiltration rates using a random-effects approach. Risk ratios or odds ratios and 95% confidence intervals (CIs) were used to describe pooled estimates for risk factors. The literature search retrieved 2548 hits, of which 59 studies were included in qualitative synthesis, and finally 10 studies were included in the meta-analysis. Studies were divided into those reporting autopsies and those reporting changes of serum transaminase levels. The majority of liver autopsies showed fatty infiltration, 82% (95% CI 39-97%) or necrosis of the liver, 18% (95% CI 13-24%). Heterogeneity in studies on hepatic functional damage following severe burns was high. Only a few were well-designed and published in recent years. Many studies could not be included because of insufficient numerical data. There is a high number of patients dying from burns that present with fatty infiltration or necrosis of hepatic tissue. Transaminases were elevated during the initial days postburn. Further research on how severe burns affect the hepatic function and outcome, especially long-term, is necessary. Systematic review registration: PROSPERO:CRD42020206061.